A comprehensive review on the diverse pharmacological perspectives of Terminalia chebula Retz. Issue 8 (August 2022) - Hassan Bulbul, Md. Rakibul; Uddin Chowdhury, Mohammad Nizam; Naima, Taslima Anjum; Sami, Saad Ahmed; Imtiaj, Md. Shakil; Huda, Nazmul; Uddin, Md. Giash
Abstract: Terminalia chebula Retz, commonly known as 'Haritaki/Myrobalan, ' has been utilised as a traditional medicine for a long time. It has been extensively exercised in various indigenous medicine practices like Unani, Tibb, Ayurveda, and Siddha to remedy human ailments such as bleeding, carminative, dysentery, liver tonic, digestive, antidiarrheal, analgesic, anthelmintic, antibacterial and helpful in skin disorders. Studies on the pharmacological effects of T. chebula and its phytoconstituents documented between January, 1996 and December, 2021 were explored using various electronic databases. During the time mentioned above, several laboratory approaches revealed the biological properties of T. chebula, including antioxidative, antiproliferative, anti-microbial, proapoptotic, anti-diabetic, anti-ageing, hepatoprotective, anti-inflammatory, and antiepileptic. It is also beneficial in glucose and lipid metabolism and prevents atherogenesis and endothelial dysfunction. Different parts of T. chebula such as fruits, seeds, galls, barks extracted with various solvent systems (aqueous, ethanol, methanol, chloroform, ethyl-acetate) revealed major bioactive compounds like chebulic acid, chebulinic acid, and chebulaginic acid, which in turn proved to have valuable pharmacological properties through broad scientific investigations. There is a common link between chebulagic acid and chebulanin with its antioxidant property, antiaging activity, antiinflammatory, antidiabetic activity, and cardioprotective activity. The actions may be through neutralizing the free radicals responsible for producing tissue damage alongside interconnecting many other diseases. The current review summarises the scientifically documented literature on pharmacological potentials and chemical compositions of T. chebula, which is expected to investigate further studies on this subject. Abstract : Terminalia chebula ; Myrobalan; Haritaki; Phytochemistry; Pharmacological activities.